Neurodidactics and Neurolinguistics: New Approaches to Teaching and Foreign Language Learning (Eurasian Journal of Learning and Academic Teaching, 2025)
In recent decades, the convergence of neuroscience, linguistics, and education has produced fertile ground for rethinking traditional pedagogical practices. Two interrelated fields—neurodidactics and neurolinguistics—have emerged at the intersection of cognitive neuroscience and instructional design, offering new theoretical insights and practical tools for more effective teaching and deeper language acquisition.